Editorial Vol7 no2 - Graham Connelly (Scottish Journal of Residential Child Care)
It gives me great pleasure to introduce this special edition of the Scottish Journal of Residential Child Care, devoted entirely to the education of looked after children and young people. Twenty-one years ago when Sonia Jackson published her influential monograph on the educational disadvantages faced by children in the care system, I was undertaking a part-time secondment with the Open University which was then developing a distance learning course for the Certificate in Social Service. Jackson's work came up in a literature search (Jackson, 1987). As a former secondary school teacher, by now working with care staff, I found Jackson's characterisation of the typical educational experiences of children in care (low attainment and disrupted schooling, low expectations and a lack of attention to education by carers, teachers and social workers, problems with literacy, lack of access to books and poor study facilities) made compelling reading, and I later wrote a whole supplement on these issues for a new edition of the OU course.